(untitled) (Research, Society and Development, 2021)
The objective of this research was to determine the levels of chlorophyll and vitamin-C in the cultivars of lettuce (Elba, Cristina and Veneranda) in the hydroponic system with nutrient solutions with different levels of salinity. The experiment was conducted at the State University of Paraíba,UEPB Campus-II, rural area of the city of Lagoa Seca-PB, using the Laminar Flow of Nutrients-NFT technique in a protected environment. The experimental design was in randomized blocks, in a subdivided plot scheme, the plots consisting of seven nutrient solutions prepared from the Furlani methodology so that solution S1 presented Electric conductivity-EC (1.9 dS m-1) and the other solutions, EC values: S2-2.4; S3-2.9; S4-3.4; S5-3.9; S6-4.4 and S7-4,9 dS m-1, with three repetitions. The subplots composed of the cultivars Elba, Cristina and Veneranda. Variables analyzed: levels of total chlorophyll (Chl a and b), carotenoids and vitamin-C. The nutritional solutions showed linear behavior for all treatments, not differing statically from each other. The highest value for total chlorophyll was obtained in the cultivar Veneranda. For the variables (Chl b and total) the highest levels were found in the cultivar Veneranda whose values 35.97 and 52.06 mg g-1 respectively. The treatment Elba/S3=3.4 dS m-1 provided the highest average carotenoid content of 57 mg g-1, yet the cultivar Elba showed the highest levels (Chl a) with nutrient solutions S2=2.4 and S3=3.9 dS m-1. The cultivar Veneranda promoted the highest levels for (Chl b and total). The highest levels of vitamin-C were found in the cultivars Cristina and Veneranda.